FAKTOR FAKTOR YANG MENENTUKAN KEPUASAN KONSUMEN PDAM DI KOTA SELONG KABUPATEN LOMBOK TIMUR PROVINSI NUSA TENGGARA BARAT - Sahrul Ihsan (Sekolah Tinggi Ilmu Ekonomi AMM, 2016)
This study aims to identify the factors that determine customer satisfaction PDAM Kota Selong East Lombok NTB and to analyze and determine which factors are a priority consideration in order to improve the performance of PDAM Kota Selong. The results showed that (1). There are ten dimensions of service quality, namely: Reliability, responsibility, competence, access, courtesy, communication, credibility, security, understanding, and tangibles. (2). Implementation of all the dimensions that build service quality PDAM Kota Selong East Lombok district generally has not met the expectations of consumers, that is new to meet the expectations of consumers in the range of 49.41% to 69.09%. (3). Based on factor analysis obtained four factors that priority decisions in an effort to improve customer satisfaction. Factor 1, includes the dimensions of responsibility, reliability and access. Factor 2, covering the dimensions of courtesy and communication. Factor 3 includes dimension credibility and understanding. Factor 4, includes the dimensions of the security dimension. (4). There are several items to consider East Lombok Water in each dimension in order to improve customer satisfaction. Items for reliability include the fulfilment of the promise and the smooth working system. Responsibility includes the will, the desire and readiness of employees in carrying out the task to assist consumers in meeting their needs